Develop time distribution pattern of design rainfall in Selangor / Mohd Nasharuddin Puteh - Puteh, Mohd Nasharuddin (2007)
Drainage practices and methods which have been developed in other countries may not always be suitable for application in Malaysia. It is very important how the time distribution of the design rainfall is determined because changes in the time distribution may vary runoff characteristics in peak flow and largely altered shape of a hydrograph calculated. Design rainfall is often required in engineering practice such as design of hydrologic structures, flood plain management, river ecological studies and flood insurance studies. A design rainfall event is specified by a rainfall duration, average rainfall intensity of a particular average recurrence interval (ARI) and rainfall temporal pattern. A rainfall temporal pattern gives the proportion of total rainfall in different periods within a given rainfall duration. In this study the rainfall data from five rainfalls stations at Sungai Selangor catchments have been used. The objective of this study is to develop the design rainfall Temporal Patterns for three selected durations (30 minutes, 60 minutes and 120 minutes). The techniques that known as the 'Method of Average Variability' have been adopted to derive design rainfall Temporal Patterns for these three selected durations. This research focuses on the design rainfall patterns.